Pengaruh Relationship Marketing, Keamanan Dan Kualitas Pelayanan Terhadap Loyalitas Melalui Kepuasan Sebagai Variabel Intervening (Studi Kasus Pada Online Shop Monokrom Store Malang) - Ainun Alifah; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis Study aims to determine and analyze the effect of relationship marketing, security, service quality on customer loyalty and customer satisfaction as an intervening variable for customer who shop at the Monokrom Store, Malang. In this study researchers have a sample of customers who have made as many as 1,950 respondents who shop online at Malang’s Monokrom Store in April 2019 by calculating using the slovin formula that shows the results of 95 respondets. Data collection is done by distributing questionnaires to customers. The analysis used in this study is to use a validity test, reliability test, normality test, path analysis, t test and sobel test. The result of this study indicate that relationship marketing, security and service quality have an indirect effect on customer loyalty, while customer satisfaction can mediate the effect of relationship marketing, security and service quality on customer loyalty.Keywords : Relationship Marketing, Security, Service Quality, Customer Satisfaction and Loyality.